The implant passport: a tool for implant maintenance and post-operative care. (2nd December 2022) - Grewal, Kuljit Kaur; Daly, Alex; Trainor, Jenna
Abstract : This article discusses the use of an implant passport to document and standardize important information relating to specific implant treatment for both the patient and their present and future clinicians. This aims to facilitate monitoring and provide salient information for any future clinician providing implant care. CPD/Clinical Relevance: The implant passport is a useful aid to deliver information concisely and accurately to the patient's GDP